“Pengaruh Kualitas Layanan terhadap Minat Berkunjung Kembali pada Hotel X di Surabaya” - Vicky Ardiansyah; Sugiharto Sugiharto; Bambang Karnain; Harsono Teguh Santoso; Achmad Daengs GS (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to determine the effect of service quality on return visit interest at hotel X in Surabaya both simultaneously and partially, and to determine the most dominant variable in influencing return visit interest. This study belongs to the type of causal research with a quantitative approach. The sample used was 96 respondents, the results of which will be tested for validity and multiple linear regression analysis, multiple determination coefficients, F test, t test, and dominant test. The study results show that service quality affects the interest in revisiting hotel X in Surabaya both simultaneously and partially. The service quality variable is the most dominant variable in influencing return visit interest at hotel X in Surabaya. Furthermore, the ability of the service quality variable to influence the revisit interest variable is 50.5%, while the remaining 49.5% is influenced by other variables not discussed in this study.